Diversifikasi Minuman Kaleng atau Botol (Studi Kasus: Strategi Diversifikasi Produk You C 1000) Persfektif UUPK - Nia Puspita Hapsari; Suhendar Sulaiman; Endang Ruswanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Product diversification is a strategy generally implemented by Fast Moving Consumer Goods (FMCG) companies to expand the market, and increase competitiveness. However, this strategy must be implemented by paying attention to consumer protection aspects as regulated in Law No. 8/Th.1999 concerning Consumer Protection (UUPK). This Study aims to analyze the product diversification strategy of You C 1000 canned, and bottled beverages from the persfective of UUPK, especially regarding consumer rights, and obligations, and the responsibilities of business actors. The study uses a qualitative approach with a case study method through secondary data analysis in the form of library documents, statutory regulations, and scientific literature in the field of marketing and consumer protection law. The results of the study indicate that the product diversification strategy of You C 1000 through the development of flavor variants, and packaging innovations to obtain a safe, and beneficial products. However, the company needs to ensure that health benefit claims are conveyed honestly, correctly, and not misleadingly to avoid violating the provisions of Articles 8 and 9 of UUPK. Research confirms that product diversification is not only orinted towards business growth, but must also prioritize the principles of legal responsibility, and consumer protection in order to create fair, and sustainable business practices.